2019
DOI: 10.1158/1078-0432.ccr-18-3517
|View full text |Cite
|
Sign up to set email alerts
|

Targeting High Mobility Group Box-1 (HMGB1) Promotes Cell Death in Myelodysplastic Syndrome

Abstract: Purpose: Myelodysplastic syndrome (MDS) is associated with a dysregulated innate immune system. The purpose of this study was to determine whether modulation of the innate immune system via high mobility group box-1 (HMGB1) could reduce cell viability in MDS.Experimental Design: We quantified HMGB1 in an MDS cell line MDS-L and in primary MDS cells compared with nonmalignant hematopoietic cells. We performed loss-offunction studies of HMGB1 using pooled siRNAs and a small-molecule inhibitor sivelestat compared… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
3
22
0
Order By: Relevance
“…It is known to function as a mediator of inflammatory processes by binding to its receptors including RAGE and a subset of TLRs (44). HMGB1 has been shown to be present in MDS marrow plasma at greater than three times the levels seen in normal marrow plasma (45,46), similar to the levels seen in the TIRAP model presented here, providing functional relevance to the role of HMGB1 in BMF syndromes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is known to function as a mediator of inflammatory processes by binding to its receptors including RAGE and a subset of TLRs (44). HMGB1 has been shown to be present in MDS marrow plasma at greater than three times the levels seen in normal marrow plasma (45,46), similar to the levels seen in the TIRAP model presented here, providing functional relevance to the role of HMGB1 in BMF syndromes.…”
Section: Discussionsupporting
confidence: 75%
“…However, S100A8 and S100A9 have also been shown to cause an erythroid differentiation defect in Rps14-haploinsufficient HSPC in a cellautonomous manner (22). Although HMGB1 has been shown to be present at high levels in MDS marrow plasma, the role of this alarmin in the disease phenotype has not been studied (45,46). Our data with TIRAP-induced BMF suggests that Caspase-1 mediated pyroptosis is not a driving factor for the observed BMF, as TIRAP expression in Casp1 -/cells did not rescue TIRAP-induced BMF or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This group used combined siRNAs and the small molecule inhibitor sivelestat to study the loss of function of HMGB1 compared to standard chemotherapy. In MDS cells, sivelestat, a neutrophil elastase inhibitor, increases the expression of PUMA and DNA double-strand breaks and activates caspase-3, which indicates that sivelestat can downregulate HMGB1 and suppress the TLR and NF-κB pathways to promote apoptosis in the BM [99]. The reduction in HMGB1 levels is sufficient to impair MDS cell self-renewal and promote apoptotic cell death.…”
Section: Myelodysplastic Syndromesmentioning
confidence: 99%
“…In our study, Con A significantly upregulated the expressions of TLR2 and TLR4 and downstream molecules and activated NF-κB, while deficiency of serotonin attenuated the influence. HMGB1, which is involved in Con A-treated mice, is acknowledged as an important ligand of TLRs [49][50][51]. We demonstrated that serotonin could stimulate the release of HMGB1, suggesting that serotonin may regulate inflammation response and aggravate liver injury via activating HMGB1-TLR signaling pathways in Con A-treated mice.…”
mentioning
confidence: 74%